The oldest 'Megapodagrionidae' (Odonata, Zygoptera) discovered in the Lower Cretaceous Yixian Formation, China. (April 2018) - Huang, Diying; Azar, Dany; Nel, André
Abstract: Cretapodagrion sibelleae gen. et sp. nov., oldest representative and first Mesozoic 'Megapodagrionidae', is described on the basis of a complete wing from the Lower Cretaceous of Yixian Formation (ca. 124.6 Ma) in China. It shows some similarities with the three extant genera of the 'Megapodagrioninae' and the enigmatic genus Mesopodagrion .